Curcumin and selenium synergistically mitigate oxidative stress in white-feathered broilers - He, Zixuan; Lin, Zhaoyan; Yan, Ye; Wang, Jiao; Zhang, Shizhong; Zheng, Bohan; Huang, Xiaohong (Frontiers in Veterinary Science, 2025)
IntroductionOxidative stress is closely linked to various diseases in chickens, representing an urgent concern that needs to be addressed in the poultry industry. Curcumin (CUR) and selenium (Se) are both recognized for their great antioxidant effects, however, the combination use of them in broilers has not been reported. This study aims to demonstrate the synergistic antioxidant effects of CUR and Se in vitro and in vivo, and to explore the underlying antioxidant mechanism.MethodsThe experiments were conducted on the DF-1 cell line and 400 healthy male White-feathered Broilers, day old, weighing 43.89 ± 0.70 g. Hydrogen peroxide (H₂O₂) and dexamethasone (Dex) were used to conduct oxidative stress model.ResultsThe results demonstrated that CUR and Se synergistically enhanced the antioxidant capacity of DF-1 cells, with a combination index (CI) less than 1; next, CUR and Se increased the total antioxidant capacity and superoxide dismutase (SOD) activity, decreased lactate dehydrogenase (LDH) and malondialdehyde (MDA) levels in broiler liver and heart tissues, alleviated Dex-induced liver and heart injury and liver cell apoptosis in broilers; moreover, the protein expression of IGF-1, PI3K-p110β, phosphorylated AKT and phosphorylated mTOR in liver and heart tissues were increased after the combination treatment.DiscussionIn conclusion, CUR and Se alleviate oxidative stress in White-feathered Broilers synergistically, and the synergistic antioxidant effects are related to IGF-1/PI3K/AKT/mTOR pathway.